2014
DOI: 10.1073/pnas.1320217111
|View full text |Cite
|
Sign up to set email alerts
|

Far transfer to language and math of a short software-based gaming intervention

Abstract: Executive functions (EF) in children can be trained, but it remains unknown whether training-related benefits elicit far transfer to real-life situations. Here, we investigate whether a set of computerized games might yield near and far transfer on an experimental and an active control group of low-SES otherwise typically developing 6-y-olds in a 3-mo pretest-training-posttest design that was ecologically deployed (at school). The intervention elicits transfer to some (but not all) facets of executive function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
16

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 40 publications
1
93
0
16
Order By: Relevance
“…In our study, we took these factors into account by using different tasks to train the target processes (and to increase the probability of generalization), by introducing two different control conditions (active and passive), and by considering motivational variables associated with training. Thus, the active control group engaged in tasks essentially requiring processing speed (for related approaches see Goldin et al, 2014; Lawlor-Savage and Goghari, 2016), in order to keep participants’ motivation and engagement similar to those from the experimental groups. Importantly, all trained participants (including the AC group) showed a meaningful improvement in the specifically trained process (IC, WM and processing speed).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we took these factors into account by using different tasks to train the target processes (and to increase the probability of generalization), by introducing two different control conditions (active and passive), and by considering motivational variables associated with training. Thus, the active control group engaged in tasks essentially requiring processing speed (for related approaches see Goldin et al, 2014; Lawlor-Savage and Goghari, 2016), in order to keep participants’ motivation and engagement similar to those from the experimental groups. Importantly, all trained participants (including the AC group) showed a meaningful improvement in the specifically trained process (IC, WM and processing speed).…”
Section: Discussionmentioning
confidence: 99%
“…During recent years, several studies have shown that EF can be improved following a systematically-increasing EF-demand schedule [70][71][72][73][74][75][76][77][78][79]. However, few of those trainings have been conducted by teachers in classes.…”
Section: Interventions Aimed At Optimising Cognitive Functioningmentioning
confidence: 99%
“…(Mejía-Rodríguez, 2009;Goldin, 2014;Mainer, 2006). En conjunto con el tópico de las capacidades de la resolución de problemas, comenzará a indagarse el aprendizaje de competencias, así como la activación de esquemas y la memorización con anclaje en el videojuego.…”
Section: Tendencias De Análisis De Videojuegos En América Latina Y Esunclassified
“…Como queda reflejado el enfoque de estos análisis excede a los contenidos de los videojuegos, no obstante es significativo que los estudios hayan pasado de la utilización de arcades de rápidos reflejos a los análisis que implementaban videojuegos con gameplay extendida como juegos de simulación, rol, estrategia en tiempo real y otros que destacaban por tener final abierto y, como lo describen diversos autores, fuerte anclaje en una cultura de pares. 13 En Argentina, la línea explicativa que reúne entrenamiento cognitivo y neurociencias ha sido desarrollada por el equipo de Goldin (2014), quienes han documentado modificaciones en funciones cognitivas especificas a través del videojuego (pero no se sabe si las mismas pueden ser trasladadas a otros contextos). Por ello, la validez ecológica de los resultados siempre es un coto infranqueable entre educación, aprendizaje y juego, pero, como veremos en el tercer capítulo, estos umbrales están relacionados con la estratificación de las prácticas lúdicas.…”
Section: Tendencias De Análisis De Videojuegos En América Latina Y Esunclassified